2021
DOI: 10.1161/circheartfailure.120.007975
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Treatment of Right Heart Failure in Pulmonary Vascular Diseases: A National Heart, Lung, and Blood Institute Workshop

Abstract: Right ventricular dysfunction is a hallmark of advanced pulmonary vascular, lung parenchymal, and left heart disease, yet the underlying mechanisms that govern (mal)adaptation remain incompletely characterized. Owing to the knowledge gaps in our understanding of the right ventricle (RV) in health and disease, the National Heart, Lung, and Blood Institute commissioned a working group to identify current challenges in the field. These included a need to define and standardize normal RV structure and function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…The right ventricle, however, is more affected in pulmonary hypertension. The failing right ventricle has only recently received more attention, [ 79 , 130 , 261 ] and the coronary circulation in right ventricular failure has received little attention at all. Yet, there are some special considerations to the coronary circulation in the right ventricle, [ 35 ] since coronary perfusion pressure is above right ventricular pressure throughout the cardiac cycle such that extravascular compression and diastolic duration during tachycardia are of lesser importance than in the LV.…”
Section: Heart Failure Of Ischemic and Non-ischemic Originmentioning
confidence: 99%
See 1 more Smart Citation
“…The right ventricle, however, is more affected in pulmonary hypertension. The failing right ventricle has only recently received more attention, [ 79 , 130 , 261 ] and the coronary circulation in right ventricular failure has received little attention at all. Yet, there are some special considerations to the coronary circulation in the right ventricle, [ 35 ] since coronary perfusion pressure is above right ventricular pressure throughout the cardiac cycle such that extravascular compression and diastolic duration during tachycardia are of lesser importance than in the LV.…”
Section: Heart Failure Of Ischemic and Non-ischemic Originmentioning
confidence: 99%
“…Patients with chronic pulmonary hypertension have reduced right coronary artery blood flow in proportion to right ventricular hypertrophy [ 257 ] and reduced adenosine-recruitable coronary reserve on MRI [ 262 ]. A recent NIH consensus workshop recommended directions for future research on the genetic, molecular and cellular processes in right heart failure, [ 130 ] but further research on the coronary circulation in right heart failure is also warranted. Arrhythmogenic right ventricular cardiomyopathy is a relatively infrequent form of human heart failure, caused by genetic mutations mostly in desmosomal proteins and characterized morphologically by diffuse fibrosis and inflammatory infiltration [ 68 ].…”
Section: Heart Failure Of Ischemic and Non-ischemic Originmentioning
confidence: 99%
“…These knowledge gaps impair patient management and may adversely impact clinician decision-making and overall clinical outcomes. It remains to be determined how factors such as demographics, comorbidities and modifiable risk factors influence RV function across the lifespan 5 6. Also unclear is how variations in genomic, proteomic and metabolomic profiles influence RV physiology in normal and diseased states, which may guide identification of novel therapeutic targets 6.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…Early on, it was concluded that a normally functioning RV ‘is not necessary for the maintenance of a normal circulation’3 and one whose function was limited to that of a conduit between the venous and pulmonary circuits 4. However, the centrality of the RV to normal cardiovascular and pulmonary physiology, as well as symptom burden and overall outcomes in cardiovascular and pulmonary disease, is increasingly recognised 5 6. Nevertheless, large gaps in knowledge persist regarding function of the RV in normal healthy individuals, as well as RV pathophysiology in cardiovascular and pulmonary disease, and finally, effective methods for managing RV dysfunction in these populations 5 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation